2020
DOI: 10.1101/2020.02.26.965269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mechanism for the extension and unfolding of parallel telomeric G-quadruplexes by human telomerase at single-molecule resolution

Abstract: 1Telomeric G-quadruplexes (G4) were long believed to form a protective structure at telomeres, 2 preventing their extension by the ribonucleoprotein telomerase. Contrary to this belief, we have 3 previously demonstrated that parallel-stranded conformations of telomeric G4 can be extended 4 by human and ciliate telomerase. However, a mechanistic understanding of the interaction of 5 telomerase with structured DNA remained elusive. Here, we use single-molecule fluorescence 6 resonance energy transfer (smFRET) mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…However, not all G-quadruplexes are refractory to telomerase extension. Parallel G-quadruplexes, whether intermolecular or intramolecular, can be bound and extended by both ciliate and human telomerase [ 39 , 155 , 159 , 160 ]. The 3′ end of the DNA aligns correctly with the RNA template of telomerase [ 39 , 159 ], and telomerase then unwinds the rest of the G-quadruplex as it extends the DNA [ 160 ].…”
Section: G-quadruplexes At Telomeric Overhangs: Effects On Their Ementioning
confidence: 99%
See 2 more Smart Citations
“…However, not all G-quadruplexes are refractory to telomerase extension. Parallel G-quadruplexes, whether intermolecular or intramolecular, can be bound and extended by both ciliate and human telomerase [ 39 , 155 , 159 , 160 ]. The 3′ end of the DNA aligns correctly with the RNA template of telomerase [ 39 , 159 ], and telomerase then unwinds the rest of the G-quadruplex as it extends the DNA [ 160 ].…”
Section: G-quadruplexes At Telomeric Overhangs: Effects On Their Ementioning
confidence: 99%
“…Parallel G-quadruplexes, whether intermolecular or intramolecular, can be bound and extended by both ciliate and human telomerase [ 39 , 155 , 159 , 160 ]. The 3′ end of the DNA aligns correctly with the RNA template of telomerase [ 39 , 159 ], and telomerase then unwinds the rest of the G-quadruplex as it extends the DNA [ 160 ]. It should be noted, however, that the preferred substrate of telomerase is linear DNA; the affinity for parallel G-quadruplexes is about 5-fold lower than their corresponding linear oligonucleotides, and accommodation of the relatively bulky G-quadruplex in the active site results in a decrease in the affinity of telomerase for incoming nucleotides [ 39 , 159 ].…”
Section: G-quadruplexes At Telomeric Overhangs: Effects On Their Ementioning
confidence: 99%
See 1 more Smart Citation
“…However, hTERT is able to extend parallel, intermolecular G4s conformations in vitro and this ability is conserved among evolutionarily distant species [ 92 ]. In fact, recent data reveal that hTERT acts as a parallel G4 resolvase [ 93 ]. In addition, hTERT is involved in mitochondrial apoptosis induced by targeted inhibition of BCL2 [ 94 ], regulates the chromatin state and DNA damage response [ 95 ] and promotes c-MYC and WNT-driven cellular proliferation [ 96 ].…”
Section: Relevant Quadruplex Structures Involved In Cancermentioning
confidence: 99%
“…Several synthetic G-quadruplex stabilizing small molecules such as telomestatin, BRACO-19, and TMPyP4, have demonstrated potential anticancer properties [21,22]. Recently however, several reports established that human telomerase could recognize, unwind, and extend intra-and interparallel G-quadruplex conformations in vitro and that they are colocalizing in vivo [14,23]. Moreover, Jansson et al recently demonstrated that G-quadruplexes can form within actively extending telomerase [24].…”
Section: Introductionmentioning
confidence: 99%